The Lateral Occipito-temporal Cortex Is Involved in the Mental Manipulation of Body Part Imagery - Kikuchi, Mitsuru; Takahashi, Tetsuya; Hirosawa, Tetsu; Oboshi, Yumi; Yoshikawa, Etsuji; Minabe, Yoshio; Ouchi, Yasuomi (Frontiers in Human Neuroscience, 2017)
The lateral occipito-temporal cortex (LOTC), including the extrastriate body area, is known to be involved in the perception of body parts. Although still controversial, recent studies have demonstrated the role of the LOTC in higher-level body-related cognition in humans. This study consisted of two experiments (E1 and E2). The first (E1) was an exploratory experiment to find the neural correlate of the mental manipulation of body part imagery, in which brain cerebral glucose metabolic rates and the performance of mental rotation of the hand were measured in 100 subjects who exhibited a range of symptoms of cognitive decline. In E1, we found that the level of glucose metabolism in the right LOTC was significantly correlated with performance in a task involving mental manipulation of the hand. Next, in E2, we performed a randomized, double-blind, controlled intervention study (clinical trial number: UMIN 000018310) in younger healthy adults to test whether right occipital (corresponding to the right LOTC) anodal stimulation using transcranial direct current stimulation (tDCS) could enhance the mental manipulation of the hand. In E2, we demonstrated a significant effect of tDCS on the accuracy rate in a task involving mental manipulation of the hand. Although further study is necessary to answer the question of whether these results are specific for the mental manipulation of body parts but not non-body parts, E1 demonstrated a possible role of the LOTC in carrying out the body mental manipulation task in patients with dementia, and E2 suggested the possible effect of tDCS on this task in healthy subjects.